Photoelectrocatalytic degradation of Rhodamine B by spray deposited Bi2WO6 photoelectrode under solar radiation. (March 2022) - Pedanekar, R.S.; Madake, S.B.; Narewadikar, N.A.; Mohite, S.V.; Patil, A.R.; Kumbhar, S.M.; Rajpure, K.Y.
Highlights: Chemical spray pyrolysis technique has been used to synthesize Bi2 WO6 thin films. Crystalline, optical, morphological and photoelectrochemical performance of Bi2 WO6 photoelectrode has been studied. Structural analysis of the Bi2 WO6 carried out by using Rietveld refinement method. Photocatalytic and photoelectrocatalytic performance of large area (10 × 10 cm 2 ) Bi2 WO6 catalyst under solar radiation have been studied. Abstract: In this work, visible region active Bi2 WO6 thin films with variable thickness are successfully deposited by simple and effective spray pyrolysis technique. The structural, optical, morphological and photoelectrochemical properties of synthesized thin films were studied. Rietveld refinement of the structural data tested purity and degree of crystallinity of Bi2 WO6 thin films synthesized with variable solution quantity. Optical study revealed visible light absorption of films and small variation in band gap energy. A thin film deposited with 70 ml spraying solution quantity exhibit higher photocurrent density (460 mA/cm 2 ) and same film with large area (10 × 10 cm 2 ) was used for photocatalytic and photoelectrocatalytic degradation of Rhodamine B (RhB) dye under solar radiation. The photoelectrocatalytic removal of RhB exhibit higher degradation efficiency (94%) as compared to photocatalytic process (23%). This study can trigger potential application of Bi2 WO6 photoelectrode in solar energy conversion, wastewater treatment and energy production. Graphical abstract: Image, graphical abstract